Regulatory T cells define affinity thresholds for CD8+ T cell tumor infiltration - Mona O. Mohsen; Romano Josi; Sanjana V. Marar; Anish Ghimire; Lan Yang; Pascal S. Krenger; Arnau Solé Casaramona; Daniel E. Speiser; Simone De Brot; Martin F. Bachmann (npj Vaccines)
Abstract TCR repertoires against tumors lack high-affinity TCRs and are further suppressed by Tregs. We hypothesized that Treg depletion enhances the antitumor efficacy of low-affinity T cells. Using the weak agonistic peptide A4Y derived from LCMV glycoprotein peptide p33 as a model antigen and VLPs as a vaccine platform, we tested this approach. In a separate low-affinity model, we targeted B16F10 melanoma with our multi-target vaccine. Results revealed limited in vivo lytic cross-reactivity between A4Y and p33 peptides, and the A4Y-vaccine alone failed to inhibit B16F10p33 tumor progression. However, combining A4Y-vaccine with Treg depletion triggered a robust immune response, characterized by increased CD8+ T cell infiltration, enhanced T cell functionality, and tumor-free survival. Infiltrating T cells also exhibited closer spatial proximity and heightened migration from blood vessels. Similarly, combining low-affinity vaccine with Treg depletion enhanced antitumor responses. These findings highlight the potential of Treg depletion to advance vaccination strategies targeting TAAs with low-affinity T cells.